#TITLE_ALTERNATIVE# - Hidayat, Aceng
Abstract A contingent valuation survey was conducted in Margahayu Raya Human Settelment, Bandung City, Indonesia, to estimate houshold's willingness to pay (WTI') for improving water debit services from Drinking Water District Company Bandung City (PDAM Kotamadya Bandung) and ground water metering system. About 102 randomly selected households who have had connection to PDAM Kotamadya Bandung were interviewed Contingent Valuation Method sees that marketless of water reources is the main reasson in pricing water difficulty so that happened what we say market failure. The marketless could be solved by contingent market. Market failure is the main contributor of availability ineficiency of water allocation and ground water over exploitation. Whereas, the price stated by government is no expression of user WTP. This WTP study is hoped to be a consideration in water pricing so that it could diminish inefficiency of water allocation and prohibit over exploitation of ground water effectively. Based on demand theory, WTP is a function of variables of household income (C), education level (E), members of family (C), water quality (Q) and behavior of water utilization of respondent including cooking/drinkng, bathing, washing (clothes, kitchen equipment, cars) and watering plant, which all of variables form multivariable regression equation. Two equation of multivariable regression found in this research is statistically significant to estimate household's WTP, both for improving of water debit services of drinking water district company and ground water metering system with household income level is the most influence variable. Respondents having higher income have higher WTP and they having lower income have lower WTP. In other hand, the higher they have income, the higher they have WTP and the lower they have income, the lower they have WTP. The average WTP for improving of water debit services is Rp 1504/m3, with the maximum WTP is Rp 3750/m3 and the minimum WTP is Rp 500/m3. Whereas, the average WTP for ground water metering system is Rp 470/m3, with the maximum WTP is Rp 1000/m3 and the minimum WTP is Rp 100/m3.